Penerapan Metode DMAIC untuk Mengurangi Breakdown Mesin Counting pada Proses Kemas Sekunder di PT Minuman Berenergi - Wardana, Muhammad Dava; Kustiwan, Susan; Widya, Adi Rusdi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to reduce the breakdown frequency of counting machines in the secondary packaging area using the DMAIC (Define, Measure, Analyze, Improve, Control) method. The main cause of breakdowns (47% of total incidents from March to April 2025) was sensor holder instability due to thin material (1 mm thickness). The improvement was made by replacing the sensor holder with 3 mm thick Stainless Steel SS304 and adding structural reinforcement. As a result, breakdown frequency decreased from 4 to 0 incidents (100% reduction), waste pack decreased from 3.2% to 1.5%, and cost savings of IDR 121,580,000 were achieved. This study demonstrates the effectiveness of the DMAIC method in improving machine reliability and production efficiency.